Morphophysiological responses of young oil palm plants to salinity stress - Vieira, Leticia Rios; Silva, Vivianny Nayse Belo; Casari, Raphael Augusto das Chagas Noqueli; Carmona, Paula Andrea Osorio; Sousa, Carlos Antônio Ferreira de; Souza Junior, Manoel Teixeira (Pesquisa Agropecuaria Brasileira, 2020)
The objective of this work was to assess the morphophysiological characteristics and the ionic imbalance in the substrate, roots, and leaves of young oil palm (Elaeis guineensis) plants under different levels of saline stress, following a substrate salinization protocol in which the level of salt was known. Bifid oil palm plants were subjected to different NaCl rates (0.0, 0.5, 1.0, 1.5, and 2.0 g NaCl per 100 g substrate on a dry basis), and their morphophysiological responses were evaluated for a period of 12–14 days. This protocol generated different levels of stress due to the gradients of electrical conductivity and water potential in the saturation extract of the substrate, according to the added NaCl. Based on the rates of real evapotranspiration and leaf gas exchange, the osmotic effect of the salt reflected negatively on leaf temperature, on the chlorophyll content index, and on the chlorophyll fluorescence variables. The increase in Na and Cl levels in the saturation extract culminated with the increasing availability of Ca, K, and Mg in the solution and their accumulation in the leaves. However, the plants poorly absorbed Na and Cl. The obtained results are indicative that, for a better characterization of the osmotic and ionic phases of salinity stress, it is necessary to reduce the applied level of salinity stress and to increase the evaluation period.